Peran Media Sosial WhatsApp dalam Meningkatkan Komunikasi Internal Staf Pegawai KUA Tiroang - Syah, Akmal; Jufri, Risdayanti; Suryawijaya, Achmad; Musi, Suryani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid development of digital communication technology has transformed internal communication practices within public institutions. This study aims to examine the role of WhatsApp in enhancing internal communication among staff at the Office of Religious Affairs (KUA) Tiroang. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation involving 19 staff members. The findings indicate that WhatsApp plays a significant role in accelerating information dissemination, improving coordination between leaders and staff, and supporting work efficiency and public service delivery. However, the use of WhatsApp also presents several challenges, including message misinterpretation, information overload, blurred professional boundaries, and dependence on a single communication platform. These findings suggest that while WhatsApp is effective as an internal communication medium, its use requires clear communication ethics and complementary communication channels to ensure accuracy and professionalism. Overall, WhatsApp contributes to building a more responsive and flexible communication system within KUA Tiroang.